Amherst in the World - Saxton, Martha (Amherst College Press, 2020)
In celebration of the 200th anniversary of Amherst College, a group of scholars and alumni explore the school's substantial past in this volume. Amherst in the World tells the story of how an institution that was founded to train Protestant ministers began educating new generations of industrialists, bankers, and political leaders with the decline in missionary ambitions after the Civil War. The contributors trace how what was a largely white school throughout the interwar years begins diversifying its student demographics after World War II and the War in Vietnam. The histories told here illuminate how Amherst has contended with slavery, wars, religion, coeducation, science, curriculum, town and gown relations, governance, and funding during its two centuries of existence. Through Amherst's engagement with educational improvement in light of these historical undulations, it continually affirms both the vitality and the utility of a liberal arts education.